The African turquoise killifish Nothobranchius furzeri as a model for aging research. (2018) - Reuter, Hanna; Krug, Johannes; Singer, Peter; Englert, Christoph
Abstract : Nothobranchius furzeri is an African killifish with an exceptionally short median life span of 3 to 7 months. Despite its short life span N. furzeri displays signs of aging that are highly reminiscent of mammalian aging. In 2015, reference sequences for the N. furzeri genome have been published. In addition, transgenesis and genomic engineering of killifish using CRISPR/Cas9 have been recently established. It has also been shown that N. furzeri is amenable to pharmacologic intervention. In this review we will discuss what makes N. furzeri a valuable model for research on aging and whether it could also be used for drug discovery.